2023
DOI: 10.5435/jaaos-d-23-00059
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance Trends in the Short-Term Postoperative Period for Patients Undergoing Total Joint Arthroplasty

Nicholas L. Pitaro,
Michael M. Herrera,
Husni Alasadi
et al.

Abstract: Background: Patients undergoing total joint arthroplasty (TJA) often experience preoperative/postoperative sleep disturbances. Although sleep quality generally improves > 6 months after surgery, patterns of sleep in the short-term postoperative period are poorly understood. This study sought to (1) characterize sleep disturbance patterns over the 3-month postoperative period and (2) investigate clinical and sociodemographic factors associated with 3-month changes in sleep. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To fill this knowledge gap, a research group from New York (New York, USA) conducted a retrospective analysis on a cohort of 104 patients undergoing hip or knee arthroplasty to establish where the patients are with sleep disturbance. 3 The authors deployed the PROMIS Sleep Disturbance questionnaire to assess sleep patterns at multiple timepoints: preoperatively, at two and six weeks, and at three months postoperatively. Interestingly, the study revealed that more than half of the patients (55%) had sleep disturbance within normal limits before the surgery.…”
Section: Sleep Disturbance Trends In the Short-term Postoperative Per...mentioning
confidence: 99%
“…To fill this knowledge gap, a research group from New York (New York, USA) conducted a retrospective analysis on a cohort of 104 patients undergoing hip or knee arthroplasty to establish where the patients are with sleep disturbance. 3 The authors deployed the PROMIS Sleep Disturbance questionnaire to assess sleep patterns at multiple timepoints: preoperatively, at two and six weeks, and at three months postoperatively. Interestingly, the study revealed that more than half of the patients (55%) had sleep disturbance within normal limits before the surgery.…”
Section: Sleep Disturbance Trends In the Short-term Postoperative Per...mentioning
confidence: 99%